PERSPECTIVE OF NIGERIAN BUILDING AND CIVIL ENGINEERING CONTRACTORS ON THE DETERMINANTS OF FIRM PROFITABILITY - Asuquo, Christian; Ogbu, Chukwuemeka (Journal of Surveying, Construction and Property, 2023)
Profitability is crucial to the success, growth and survival of construction firms. This study investigated the factors affecting the profitability of construction contractors in Akwa Ibom State, Nigeria. It also determined if there are differences in the perspectives of building and civil engineering contractors on the important factors affecting profitability. Data were collected with the aid of a well-structured questionnaire and were analysed using mean score and Mann-Whitney U test. A total of 173 adequately completed questionnaires were analysed. Turnover or volume of sale of the contracting firm is considered as the most important factor influencing contractors’ profitability, while other key factors include low profit margin of projects, contractor’s productivity and shortage of working capital or liquidity issue. Findings also revealed that there is a difference in the perception of building and civil engineering construction contractors on most of the factors affecting profitability of contracting firms. It is recommended that that construction contractor should create a work bank or increase the amount of construction work at hand in order to keep turnover flowing steady. In addition, the distinction between building and civil engineering contracts should be recognised when considering the factors affecting contractors’ profitability.